REMOVING COD, N AND P FROM DAIRY WASTEWATER BY EMPLOYING LACTOBACILLUS PLANTARUM WITHIN MICROBIAL ELECTROLYSIS CELL - A. W. Ahmed; M. A. Atiya; M. J. M-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study explored the capability of treating real dairy wastewater using the microbial electrochemical system by using Lactobacillus plantarum species as a microorganism. The samples were collected from a local factory for dairy products in Baghdad. Three main parameters were investigated with different levels, for estimating chemical oxygen demand (COD), phosphate (P) and nitrogen (N) removal efficiency. The studied parameters were detention time, the potential difference between electrodes and initial concentration of COD. The respective optimum values for these parameters were 17 days, 400 mV and 17000 mg COD/L respectively. At the optimum values, the optimum COD removal efﬁciency was 99.4%. Meanwhile, the study also performed removal efficiency for N and P due to their effects on the aquatic life and ecosystem. The optimum removal efficiency for P and N were 99% and 99%, respectively.